2022
DOI: 10.1111/jbi.14457
|View full text |Cite
|
Sign up to set email alerts
|

Country‐level checklists and occurrences for the world's Odonata (dragonflies and damselflies)

Abstract: Aim: Biogeographical inference and assessments of species' threat status and trends depend on comprehensive information on the current geographical distribution of species. Even country-level presences remain poorly known for many insect species and consistent global overviews for those species are missing. Here we integrate information from literature checklists, point occurrences, and identify potential species range gaps to provide a database of country-level checklists of dragonfly and damselfly species an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 68 publications
(90 reference statements)
1
14
0
Order By: Relevance
“…In addition to its importance in shaping their contemporary distribution, phylogenetically comparative analyses and distributional anomalies also indicate that niche conservatism has greatly influenced the distribution and diversification of odonates. Although Odonata are globally distributed, the greatest number of families and genera are found in tropical climates, where the group originated (Bybee et al, 2021; Sandall et al, 2022). We found that the relatively few lineages in extreme climates (both desert and arctic regions) are almost exclusively anisopteran (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its importance in shaping their contemporary distribution, phylogenetically comparative analyses and distributional anomalies also indicate that niche conservatism has greatly influenced the distribution and diversification of odonates. Although Odonata are globally distributed, the greatest number of families and genera are found in tropical climates, where the group originated (Bybee et al, 2021; Sandall et al, 2022). We found that the relatively few lineages in extreme climates (both desert and arctic regions) are almost exclusively anisopteran (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we pooled the gridded expert and ecoregional species ranges and removed duplicate cell–species combinations and cells with >50% water (i.e., with >50% of the values being not available in the mean annual temperature layer). The final distribution dataset included 5233 (83%) of all 6322 currently accepted Odonata species (Sandall et al, 2022), covering 2802 species with associated body size data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inconsistency and lack of author information for birds, daisies, and amphibians (as indicated by their GIST score) limit the ability to track name identifications over time in taxonomic knowledge assessments. The number of sources required to generate a comprehensive synonym lists for butterflies and dragonflies diminish the GIST group score but does not necessarily impede subsequent integration thanks to recent efforts [32,75] (Box 1, Figure II). Exceptions that have a relatively high GIST score but are poorly integrated are crabs, while odonates, a small taxon with a relatively large research community but a lower GIST score, are exceptionally well-integrated.…”
Section: Examining the Interoperability Of Commonly Used Data Sourcesmentioning
confidence: 99%
“…Tracking the "Species concept in space and time" GIST element represents a specific area of needed and emerging focus (Box 1, Figure I) [80,81]. Documentation of alternative names from various sources in the "Synonyms list" also represents an area of improvement to ensure globally coordinated databases within and across taxa, as recently done for butterflies and dragonflies [32,75]. Even though databases may respond to distinct codes of nomenclature [82][83][84], or models of governance [37,47], the GIST elements are simple enough to be transferrable across all databases and taxa and can rely on the DwC standards (see Online Supplemental Information Table S2) [57].…”
Section: Overcoming Barriersmentioning
confidence: 99%